2009
DOI: 10.1243/09544062jmes1672
|View full text |Cite
|
Sign up to set email alerts
|

The future of engineering tribology in concentrated contacts

Abstract: This article attempts to anticipate likely trends and developments in the field of engineering tribology. It is, of course, a personal view and the authors have chosen to focus on the field of concentrated contacts operating in elastohydrodynamic lubrication (EHL), where they are tempted to make the kind of predictions required with at least a modicum of confidence. The main thrust of the argument presented is that engineering tribology will develop considerably, and move towards modelling failure of the EHL m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…In the case of the mesoscopic stresses, the maximum shear stress spikes toward 0 when the pressure spikes. This is relevant to the application of equation (1).…”
Section: Simulation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of the mesoscopic stresses, the maximum shear stress spikes toward 0 when the pressure spikes. This is relevant to the application of equation (1).…”
Section: Simulation Resultsmentioning
confidence: 99%
“…3 Olver 4 comments on the competition between micropitting and wear: mild wear tends to suppress micropitting. In fact, Torrance et al 5 and later 1 Laine´et al 6 demonstrated that anti-wear additives ease micropitting by impeding mild wear. The relationship between wear and micropitting can be observed in the present work as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation